A new species of the genus Jungermannia (Jungermanniales, Marchantiophyta) from the Caucasus with notes on taxa delimitation and taxonomy of Jungermannia s. str. - Konstantinova, Nadezda A. A.; Vilnet, Anna A. (Phytotaxa, 2016)
The new species Jungermannia calcicola Konstant. et Vilnet, is described based on a critical reinvestigation of morphological features and molecular analyses of trnL–trnF and trnG intron cpDNA sequences of forty samples of Jungermannia s. str. The new species is described and illustrated as well as noting its differentiation from allied species and distribution patterns. New data on some taxonomical ambiguities and on the taxa delimitation in the Jungermannia s. str. are discussed.